Evaluation of the Implementation of a Home-Based Exercise Training Program for People With COPD: A Mixed-Methods Study - Cerini, Tamara; Kunz, Ramona; Dalla Lana, Kaba; Radtke, Thomas; Polhemus, Ashley; Puhan, Milo A.; Frei, Anja (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Recently, we developed a home-based, minimal-equipment exercise training program HOMEX for people with chronic obstructive pulmonary disease (COPD) and tested its effectiveness over 1 year in a randomized controlled trial. The aims of the current study were to evaluate the implementation of HOMEX from the perspectives of all involved persons and to optimize the program to ensure its long-term sustainability. Methods: In this mixed-methods study, we used qualitative and quantitative approaches to evaluate the implementation of the intervention on the level of patients with COPD and coaches who provided the intervention and relevant stakeholders. To assess the implementation outcomes dose, reach, fidelity, and adherence, we summarized information recorded in the notes of the coaches and the diaries of patients, complemented with results from qualitative assessments. To assess acceptability and appropriateness, we conducted surveys with patients and coaches, and semistructured interviews with selected patients, coaches, and stakeholders. Results: The coaches delivered the three home visits with one exception according to the protocol (fidelity). Of the 53 intervention group participants, 37 (70%) conducted HOMEX training until the end of the study and 43 (79%) trained for at least 10 months. The exercise behaviors of the participants could be separated into the phases “Starting the training and stabilizing into regular training routine” and “Managing training disruptions” (adherence). Overall, patients, coaches, and stakeholders conveyed a very high “acceptability” of HOMEX, noting the home-based aspect as a particular strength and interaction with other patients as future need. All involved groups perceived the strength-training exercises as appropriate, efficient for people with COPD, and relevant to maintain improvements after pulmonary rehabilitation. The most important facilitators of the patients for long-term motivation were self-perceived improvement in strength, supervision by a coach, and integration of the training in daily routine. Based on these insights, we redesigned and reworded the exercise cards, introduced three new exercises, and refined the training book. Discussion: The results of this study provided insights of the involved persons in the frame of the HOMEX intervention implementation with a particular focus on the long-term training behavior of the participants and their perception and experience with the exercise program. These findings enabled us to optimize the training material and adapt the structure of the program for sustainable further use in clinical and other settings.